REKONTEKSTUALISASI KITAB TURATS BIDANG NAHWU DALAM MUSABAQAH QIRA`ATIL KUTUB TINGKAT NASIONAL (MQKN) 2023 - Saumantri, Theguh (Jurnal Studi Pesantren, 2024)
The Book of Turats has a central role in Islamic boarding school education in Indonesia, being the Mandzumah book that is often taught and studied by Islamic boarding school students. The aim of this research is to examine the recontextualization of the Book of Turats in the field of nahwu in the context of the National Level Musabaqah Qira'atil Pole (MQKN) 2023. This research focuses on the understanding and application of Arabic grammar taught in the book Alfiyah Ibnu Malik. This research uses a descriptive qualitative approach with library research methods which include field studies through observation, documentation and interviews. The results of this research explain that recontextualization in the field of nahwu is assessed from several components, namely maqro (reading), meaning (understanding) of the book, and depth of analysis of the book. Overall, all participants who took part in the contest in the field of nahwu have demonstrated good qualities in reading fluently and accurately, including fashahah and intonation in reading, correct use of the I'rab character, as well as understanding and application of the sharf form. Recontextualizing the book of Turats in the context of MQKN 2023 provides an opportunity for participants to apply Arabic grammar knowledge in a broader context, especially in understanding and analyzing the text of the Qor'an and hadith.